Simulasi Penentuan Optimasi Arah Taksi Kosong Dengan Gps Dan Metode Monte Carlo - Hutapea, Sabungan Halomoan; Sinaga, Rosita (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
The development of metropolitan cihJ as Jakarta for years is high, thus the demand Jo transportationservices. Tcui is one of mode transportation which is mostly used by middle to high class people. Theproblem is, sometimes many people are wasting time for waiting empty taxi, mean while manyempty taxi, are searching for the passenger.The objective of this simulation model is to direct the taxi, movement to get passenger with the help ofi b